Manajemen Strategik dalam Peningkatan Mutu Pendidikan - Moh. Rois Abin (Institut Agama Islam Negeri (IAIN) Tulungagung, 2017)
This research is motivated by the phenomenon which is telling that education should be managed with the strategic management in order to be able to choose among a lot of good management to produce a most excellent management to be developed. This research was conducted in Madrasah Aliyah Negeri Kunir Wonodadi Blitar and Madrasah Aliyah Negeri (MAN) Blitar. The approach which was used in this study was a qualitative approach to the multi-site study. Data were collected through interviews, observation and documentation. The results of this study concluded that: Strategic planning at MAN Kota Blitar was conducted through activities, the formation of the formulating vision and mission team, the determination of the vision and mission, analyzes opportunities, threats, barriers, and alternative of the problem solving, Ma'had procurement, opening the enrichments class, increasing learning, and improving the quality of educators. Strategic evaluation in MAN Kunir was conducted through: official meetings, meeting with the headmaster and committees, special meeting headmaster and vice of headmaster, teacher, employees, and the headmaster meetings, and committee meetings. While in Madrasah Aliyah Negeri Blitar was conducted through: official meetings, meeting with the headmaster, and committees, special meeting headmaster vice of headmaster, teachers, employees, and the headmaster meeting, activities meeting.